2013
DOI: 10.5262/tndt.2013.1001.08
|View full text |Cite
|
Sign up to set email alerts
|

Reliability and Validity of the Turkish Version of the Dialysis Symptom Index in Chronic Hemodialysis Patients

Abstract: OBJECTIVE: This study was planned for the purpose of adapting and determining the reliability and validity of the Turkish version of the "Dialysis Symptom Index (DSI)" for Turkish hemodialysis patients. MATERIAL and METhOdS:This study was conducted in two dialysis units. A total of 120 hemodialysis patients participated in the research. Written permission to conduct the research was obtained from the institutions and the patients. Research data were collected using a questionnaire and the DSI. It assesses symp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
17
0
2

Year Published

2014
2014
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(20 citation statements)
references
References 6 publications
1
17
0
2
Order By: Relevance
“…In our study, two items had low kappa values including diarrhea and nausea. These results are consistent with some other studies ( 16 , 27 ). The findings of this study suggest that the DSI is a reliable and valid tool to assess physical and psychological symptoms in patients with ESRD.…”
Section: Discussionsupporting
confidence: 94%
See 3 more Smart Citations
“…In our study, two items had low kappa values including diarrhea and nausea. These results are consistent with some other studies ( 16 , 27 ). The findings of this study suggest that the DSI is a reliable and valid tool to assess physical and psychological symptoms in patients with ESRD.…”
Section: Discussionsupporting
confidence: 94%
“…The face and content validity of the questionnaire were confirmed after minor revisions. Yesilbalkan evaluated psychometric properties of the Turkish language version of the DSI and reported a good content validity for the Turkish version of the DSI ( 27 ). To establish the convergent validity of the Persian version of DSI, the DSI and SF-36 questionnaires were administered to patients.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Six validation studies reported content validity indexes (CVI) [33, 38, 49, 53, 77, 82] and of these only Suet-Ching [49] reported patient involvement in the process of content validation.…”
Section: Resultsmentioning
confidence: 99%